فلسفة العقوبة في الشريعة الإسلامية والقانون الوضعي عرض وموازنة = Exposition and comparison of the philosophy of punishment in Islamic and positive laws = Eksposisi dan perbandingan falsafah hukuman dalam undang-undang Islam dan positif - Abdul Majid, ِAbdul Majid Qasiem; Laeba, Muhammad (International Islamic University Malaysia, 2012)
In this paper light is shed on the philosophy of punishment in Islamic and positive laws and a comparison between them is accomplished. In brief, the conclusion of the exposition and comparison is that issue of infallibility of SharÊ‘ah and its nobleness are the distinguishing marks between Islamic and positive laws. This led to further differences. The first difference is that the punishment in positive laws is in accordance with the stipulated goal, that is, the goal is set first and then the punishment is formulated in that light. That is why whenever any new school of thought appears based on some ideology, differences emerge in punitive legislation. Islamic penal system is, however, immutable and infallible. There is a need to know its objectives and wisdom so as to in order to tackle new emerging issues. The nobility of the philosophy of punishment in Islamic law stems from the nobility of its source and that is no one but the Creator of human beings. The punishment in the positive law, on the other hand, relies on the philosophy that is based on the experiences of the authors of these laws. And these experiences are limited and their rulings are relativistic. Applying Islamic legal punishments are, therefore, more legitimate, even though their essence and philosophy are not fully grasped.